Mental health first aid for the UK Armed Forces. (31st January 2019) - Crone, Diane M; Sarkar, Mustafa; Curran, Thomas; Baker, Colin M; Hill, Denise; Loughren, Elizabeth A; Dickson, Tabitha; Parker, Andrew
Abstract: Education programmes in mental health literacy can address stigma and misunderstanding of mental health. This study investigated self-rated differences in knowledge, attitudes and confidence around mental health issues following participation in a bespoke Mental Health First Aid (MHFA) training course for the Armed Forces. The mixed methods approach comprised quantitative surveys and qualitative interviews. A survey, administered immediately post-training ( n = 602) and again at 10-months post-attendance ( n = 120), asked participants to rate their knowledge, attitudes and confidence around mental health issues pre- and post-training. Quantitative findings revealed a significant increase in knowledge, positive attitudes and confidence from the post-training survey which was sustained at 10-months follow-up.Semi-structured telephone interviews ( n = 13) were conducted at follow-up, 6-months post-attendance. Qualitative findings revealed that participation facilitated an 'ambassador' type role for participants. This study is the first to have investigated the effect of MHFA in an Armed Forces community. Findings show participants perceived the training to increase knowledge regarding mental health and to enhance confidence and aptitude for identifying and supporting people with mental health problems. Results suggest that such an intervention can provide support for personnel, veterans and their families, regarding mental health in Armed Forces communities.